2020
DOI: 10.7759/cureus.9557
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of YouTube Video Content About Developmental Dysplasia of the Hip

Abstract: The purpose of this study is to investigate the quality and reliability of YouTube videos regarding developmental dysplasia of the hip (DDH). Background YouTube is one of the most popular websites used as a source of information, but the variety in authorship and lack of a peer-review process are problems. Methods The search string "developmental dysplasia of the hip" was inputted to the YouTube search engine, and the first 52 videos returned as a response were assessed. The Video Power Index (VPI) (like ratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
0
15
0
2
Order By: Relevance
“…Based on GQS scoring, the quality of the viewed YouTube was found as moderate. The mean GQS score was reported as 4.00 by Onder et al [ 28 ], 3.08 by Ustdal et al [ 29 ], and 2.46 by Oztermeli et al [ 30 ] with higher GQS scores were given to the videos uploaded by health professionals. Again our higher GQS scores might be attributed to the fact that the majority of the videos were uploaded by health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Based on GQS scoring, the quality of the viewed YouTube was found as moderate. The mean GQS score was reported as 4.00 by Onder et al [ 28 ], 3.08 by Ustdal et al [ 29 ], and 2.46 by Oztermeli et al [ 30 ] with higher GQS scores were given to the videos uploaded by health professionals. Again our higher GQS scores might be attributed to the fact that the majority of the videos were uploaded by health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers accredited this to the nature of the uploaders of the videos. It has been reported that the videos uploaded by patients and their relatives are bad and misleading [ 27 ]. We found that only three of the 50 videos we examined were uploaded by patients and all of these contained misleading content.…”
Section: Discussionmentioning
confidence: 99%
“…16 It has been subsequently validated through many studies throughout orthopedic literature. 8,10,12,15,20 Videos were categorized by the source responsible for providing the video: physician, academic, commercial, nonphysician/trainer, or media. Physician videos were those originating from a private practice or produced by an individual surgeon not affiliated with an academic center, while academic videos were those produced by academic centers or surgeons.…”
Section: Methodsmentioning
confidence: 99%
“…Health-related videos published on the YouTube platform do not require editorial review or evaluation of credibility prior to being uploaded, and patients accessing this information are given no indication of material quality. Investigations into the quality and accuracy of YouTube videos have been undertaken for a wide range of orthopedic conditions and procedures, including hip and knee arthroplasty, 6 common hip and knee injuries, 7 -11 shoulder pathology, 12,13 pediatric conditions, 14,15 and spine pathology. 16 -19 In the realm of foot and ankle care, the quality of YouTube as a source of information on hallux valgus surgery and diabetic foot care has been previously studied.…”
Section: Introductionmentioning
confidence: 99%